2010
DOI: 10.1007/s00775-010-0721-3
|View full text |Cite
|
Sign up to set email alerts
|

Structural characterization of human S100A16, a low-affinity calcium binder

Abstract: The homodimeric structure of human S100A16 in the apo state has been obtained both in the solid state and in solution, resulting in good agreement between the structures with the exception of two loop regions. The homodimeric solution structure of human S100A16 was also calculated in the calcium(II)-bound form. Differently from most S100 proteins, the conformational rearrangement upon calcium binding is minor. This characteristic is likely to be related to the weak binding affinity of the protein for the calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…In contrast, buffers (signal modulators) [81] would not, and a lack of a conformational change within the EF-hand domain would indicate that a domain was a buffer. For example, S100A16, whose structure did not show any significant conformational change upon calcium binding [83] . Similarly, no significant structural changes on calcium binding were observed for the calpain C-terminal domain [84] , Cbp40 [85] and S100P [86] and they would be considered as likely buffers on this basis.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, buffers (signal modulators) [81] would not, and a lack of a conformational change within the EF-hand domain would indicate that a domain was a buffer. For example, S100A16, whose structure did not show any significant conformational change upon calcium binding [83] . Similarly, no significant structural changes on calcium binding were observed for the calpain C-terminal domain [84] , Cbp40 [85] and S100P [86] and they would be considered as likely buffers on this basis.…”
Section: Resultsmentioning
confidence: 99%
“…S100A16, a member of the S100 family, is located in an unstable region on the human chromosome, 1q21 . S100A16 is highly conserved in mammals, has diverse functions, and is highly as well as extensively expressed in diverse tissues and cells types, including the fat tissues and the brain .…”
Section: Discussionmentioning
confidence: 99%
“…It is highly conserved in mammals and found to be associated with various tumors . S100A16 expression was found upregulated in multiple cancers, such as bladder, lung, thyroid, pancreas, and ovary cancer . Furthermore, high S100A16 expression was found significantly associated with poor prognosis in lung cancer, prostate cancer, and breast cancer .…”
Section: Introductionmentioning
confidence: 98%
“…One of the suggested reasons for S100 isoform dominated interaction in Y-2H could be a function of tightly controlled intracellular Ca 2+ concentration (200nM) in yeast cell [25] which is far below the calcium K d values of many S100 proteins (10-50 µM) and that could limit interaction between S100 prey and its non-S100 interaction partners that require strict Ca 2+ concentration for the interaction to take place. Nevertheless, in contrast to many other S100 proteins, structural analyses have suggested that both S100A14 and S100A16 are low affinity Ca 2+ ion binders with minimal conformational changes after binding with Ca 2+ [26,27] and hence strict Ca 2+ concentration might not be necessary for the interaction between these two proteins. In fact, by increasing the Ca 2+ concentration, increased immunoprecipitation was not observed between S100A14 and S100A16 in the current study (Figure 1A).…”
Section: Discussionmentioning
confidence: 99%